EMPOWERMENT OF FINANCIAL LITERACY AND ACCOUNTING DIGITALIZATION FOR TRADITIONAL MARKET TRADERS ASSOCIATIONS AT DAMNOEN SADUAK FLOATING MARKET, THAILAND - Bambang Dwi Suseno; Gema Ika Sari; Sasithorn Suwandee; Hidayatullah Hidayatullah; Nining Sulastri Kurnia; Riani Puasarin; Fitriyansyah Fitriyansyah; Nani Rohaeni (International Journal of Engagement and Empowerment (IJE2), 2026)
This community service program aims to enhance financial literacy and promote accounting digitalization among traditional market traders at Damnoen Saduak Floating Market, Thailand. The program was designed to address key challenges faced by traders, including limited financial knowledge, lack of proper financial record-keeping, and low adoption of digital tools. A participatory and capacity-building approach was employed, consisting of needs assessment, training, mentoring, and evaluation using a pre-test and post-test design. The results show a significant improvement in participants’ financial literacy, as well as their ability to prepare simple financial statements and manage business finances more effectively. In addition, the adoption of digital accounting tools increased substantially, indicating a positive shift toward digital transformation. These findings demonstrate that structured community service interventions can effectively empower small-scale traders, improve their financial management practices, and enhance their competitiveness in the digital economy. However, continuous assistance and follow-up programs are necessary to ensure sustainability and long-term impact.